An investigation into the X-ray bursts in Cir X-1 - Yu, Zhuo-Li; Zhang, Shu; Zhang, Shuang-Nan; Li, Xiang-Dong; Chen, Yu-Peng; Peng, Jing-Qiang; Shui, Qing-Cang (Astronomy and astrophysics (Berlin), 2025)
We report 155 X-ray bursts from Cir X-1 detected with NICER and 48 with Insight-HXMT, respectively. The K-medoids clustering algorithm was applied to X-ray bursts detected by NICER for classification. These X-ray bursts are classified into two categories, designated as Class A and B. The profile of Class A resembles that of a typical type I X-ray burst. Class B is weaker and its profile is approximately symmetric. In these X-ray bursts, the shortest recurrence time of ∼300 s observed to date in Cir X-1 is detected. Additionally, no burst is detected prior to MJD 58933 in NICER and Insight-HXMT. The underlying reason for this phenomenon remains unclear and requires further investigation.